A microchip electrophoretic assay for DNA methyltransferase activity based on methylation‐sensitive endonuclease DpnⅡ. Issue 3 (1st August 2018) - Zhang, Yating; Zhang, Yan; Zhu, Luqi; He, Pingang; Wang, Qingjiang
Abstract: DNA methylation is a significant epigenetic modification and the methods for the detection of DNA methyltransferase (MTase) activity are important due to aberrant methylation closely related to the occurrence of cancer. In this study, a simple and rapid microchip electrophoresis (ME) coupled with LED‐induced fluorescence (LEDIF) method was presented for the detection of Dam MTase activity. This strategy was based on methylation‐sensitive endonuclease DpnⅡ which could recognize the same specific site 5′‐GATC‐3′ with Dam MTase in double‐stranded DNA (dsDNA). The adenines in the specific site could be methylated by Dam MTase, then the special site could not be digested by DpnⅡ. Both methylated dsDNA and unmethylated dsDNA could be analyzed by ME‐LEDIF after stained by SYBR gold. The results showed the fluorescence intensities of methylated dsDNA were directly proportional to Dam MTase activities in the range of 0.5–20 U/mL with a detection limit of 0.12 U/mL. Furthermore, the method could successfully be applied to evaluation experiments of Dam MTase inhibitors. The results confirmed the ME‐LEDIF method is a promising approach for inhibitors screening of DNA MTase and development of anticancer drugs